Sexual behaviour of young people in international tourist resorts. Issue 1 (30th January 2004) - Bellis, M A; Hughes, K; Thomson, R; Bennett, A
Abstract : Background/objectives: Increasingly, young people travel abroad to experience nightlife in international resorts. Although media coverage of such resorts suggests high levels of sexual activity, little empirical data are currently available. We have measured: 3 year trends in sexual behaviour of young people visiting Ibiza, levels of sexual risk taking, and their relation to substance use. Additionally, in 2002 we identified levels of homosexual sex and sexual interactions between UK residents and individuals from other countries. Methods: Data were collected from visitors to Ibiza between 2000 and 2002 just before they left the island. Information on sexual health was surveyed using a short anonymous questionnaire. Results: Over half of individuals (56.0%) visiting Ibiza had sex with at least one person, with 26.2% of males and 14.5% of females having sex with more than one individual. However, of those arriving without sexual partners (75.5%) just under half (47.5%) have sex in Ibiza and most of these (62.4%) always used condoms. Having any sex abroad was associated with using illicit drugs and having more sexual partners in the 6 months before visiting Ibiza. However, having unprotected sex or sex with more than one person was associated with smoking as well as having higher numbers of sexual partners before their visit. Overall, 8.6% of individuals had sex with a non-UK resident in Ibiza although such individuals were no more likely to have sex without condoms. Conclusions: Substantial numbers of individuals visiting international nightlife resorts have unprotected sex with people they meet while abroad. This poses an increasing threat to the sexual health of UK residents but as yet little attention has been paid to developing interventions that might reduce sexual risk taking among young people holidaying abroad.